KAJIAN POTENSI ENERGI SURYA DI PROVINSI NUSA TENGGARA BARAT (NTB) - Redaksi Tim Jurnal (Sekolah Tinggi Teknik PLN, 2016)
Generating system using solar energy technology is generally categorized into two groups, There are using of passive technology and active utilization of technology. These groupings depending on the absorption process, conversion, and distribution of solar energy. Examples of active solar energy utilization is the use of photovoltaic panels and heat absorber panel. Examples of passive solar energy utilization includes directing the building toward the sun, choose a building with thermal mass or good light dispersion capabilities, and designing the room with natural air circulation.Solar radiation intensity data in a specified area can be obtained in three ways: first, direct measurement using a measuring instrument pyranometer, pyrheliometer and Campbell stokest. Second, with the satellite imagery data, satellite imagery data is widely used because it is easily accessible globally. Third, with the numeric modeling in simulation computer for the purpose of knowing the potential radiation that will come. In an effort to encourage the use of renewable energy in the region, especially solar energy, has conducted studies of solar energy potential by conducting a preliminary survey and installation of pyranometer, in West Sumbawa regency of the Month from September to December 2015 by an average of 762.331 watts / m2.